THE AUDIOVISUAL CONNECTIONS IN THE TELEVISION COMMERCIALS - Szabo, Daniel Robert (MATTER: International Journal of Science and Technology, 2018)
Most of the television advertisements contain some sort of music, which can contribute to the stories and concepts found in them, and more importantly, to their overall messages and potential impacts, too. In this paper, the strength of the congruency or coordination between the visual elements of the ads and their music, as well as the types of these solutions, and also, the inconsistencies in this field were studied. For the sample of the present study, 100 ads from the most valuable brands served as a basis. Characteristics, like the genre and origin of the music, the inclusion of multiple or different pieces of music in each advertisement, the degree, and type of the coordination, between the music and the story of the film, as well as the types of verbal information heard in the ads were examined. The aim was to find audiovisual solutions, best practices that can be used in the marketing communication of brands.